The impact of hyaluronan-enriched culture medium and intrauterine infusion of human chorionic gonadotropin on clinical outcomes in blastocyst transfer cycles. (3rd March 2020) - Balakier, Hanna; Kuznyetsova, Iryna; Librach, Clifford L.
ABSTRACT: Over the last few decades, advances in ovarian hormonal stimulation, embryology laboratory technologies and embryo genetic testing, have significantly enhanced clinical outcomes in human assisted reproduction technologies (ART). However, embryo implantation remains a major bottleneck in achieving better pregnancy and live birth rates. Thus, there is growing interest in establishing new approaches to enhance implantation efficiency after embryo transfer. With advanced molecular techniques, many promising biomarkers associated with embryonic and endometrial changes occurring prior to and during embryo implantation have been identified. However, despite the progress in applying novel procedures into IVF practice, clinical evaluation of those biomarkers has so far reached modest predictive value for enhancing blastocyst developmental potential and endometrial receptivity. Therefore, other simpler strategies have also been introduced to increase the rates of successful clinical pregnancies and live births. One of these approaches is to investigate the impact of using embryo transfer medium containing high concentrations of an adherence compound, such as hyaluronic acid (HA), on IVF outcomes. Additionally, intrauterine infusion of a small volume of human chorionic gonadotropin (hCG) at the time of embryo transfer (ET) has also been proposed as a technique that might be advantageous for increasing the clinical outcomes, considering the fact that hCG plays a critical role in synchronizing endometrial and fetal development. However, the current findings from both interventions remain controversial, demonstrating a mixture of positive and indifferent results of these treatments in ART cycles. Further research will be crucial for a better understanding of the molecular mechanism of cross-talk between the blastocyst and the maternal endometrium during the optimal implantation period when using either hyaluronan-enriched medium or hCG infusion before embryo transfers. Therefore, this review aims to present existing literature related to both treatments, emphasizing their effects on blastocyst implantation. Abbreviations: ART: assisted reproduction technologies; HA: hyaluronic acid; hCG: human chorionic gonadotrophin; IVF: in vitro Fertilization; ET: embryo transfer; pH: hydrogen ions; CO2: Carbone dioxide; O2: Oxygen; PGT: pre-implantation genetic testing; FET: frozen embryo transfer; PCOS: Polycystic ovarian syndrome; DNA: deoxyribonucleic acid; miRNA: micro-ribonucleic acid; EVs: extracellular vesicles; ERA: endometrial receptivity array; CD44 and RHAMM: primary hyaluronan surface receptors; RCT: randomized clinical trials; LBR: life birth rate; CPR: clinical pregnancy rate; IR: implantation rate.